Spondylodiscitis Caused by Enterobacter agglomerans - Jayaweera Arachchige Asela Sampath Jayaweera; Mahen Kothalawala; Balachandran Devakanthan; Sinnappoo Arunan; Dinithi Galgamuwa; Manori Rathnayake (Case Reports in Infectious Diseases)
All over the globe, the incidence of vertebral infection is rising. Nowadays, compared to tuberculous variety, pyogenic spondylodiscitis incidence is high. The increase in the susceptible population and improved diagnostics summatively contributed to this. In clinical grounds, differentiation of pyogenic and tuberculous spondylodiscitis is well defined. Enterobacter agglomerans is a hospital contaminant and associated with infections in immunocompromised individuals and intravenous lines. It causes a wide array of infections. Enterobacter agglomerans spondylodiscitis is unusual and there are, around the globe, only less than 31 suspected cases that have been previously reported. Enterobacter agglomerans histology mimics tuberculous rather than pyogenic spondylodiscitis. A 65-year-old farming lady, while being in hospital, developed sudden onset spastic paraparesis with hyperreflexia. Later blood culture revealed Enterobacter agglomerans with 41-hour incubation in 99.9% probability from Ramel identification system. Her initial ESR was 120 mm/first hour. Isolate was susceptible to ciprofloxacin and intravenous followed with oral therapy shows a drastic ESR fall and improved clinical response. Differentiation of tuberculous and pyogenic spondylodiscitis is very much important in management point of view. Therefore, blood culture has a role in diagnosis of spondylodiscitis. ESR can be used as important inflammatory marker in monitoring the response to treatment. Retrospectively, ESR would aid in reaching a definitive diagnosis.